PELATIHAN PENGOLAHAN SINGKONG MENJADI OLAHAN MAKANAN BERVARIASI GUNA MENINGKATKAN PEREKONOMIAN KELUARGA - Eem Kurniasih; Lusi Rachmiazasi Masduki; Bambang Dalyono (STIE PGRI Dewantara Jombang, 2022)
This community service activity aims to increase cassava processing skills into various variations of food made from cassava (cassava). This activity involved members of the Family Welfare Empowerment in Jaten Village, Karanganyar - Surakarta as foster partners. This activity lasted for six months intensively with an intensive training model accompanied by the provision of supporting materials. From the results of the training, the fostered partners were able to absorb the material provided well. Supported partners can process food made from cassava into several variations of food that have economic value so that they can be sold to increase family income.